Investigation of Enteric Viruses Associated With Runting and Stunting in Day-Old Chicks and Older Broilers in Southwest Nigeria - Adebiyi, Adebowale I.; Tregaskis, Paula L.; Oluwayelu, Daniel O.; Smyth, Victoria J. (Frontiers in Veterinary Science, 2019)
Enteric viruses are known to have significant economic impact on poultry, especially broiler chicken flocks, because of production losses attributable to poor feed conversion and weight gain. To sustain the Nigerian poultry industry that contributes significantly to the livestock sector of the economy, there is a need to investigate commercial broiler flocks in the country for the presence of enteric viruses causing runting and stunting, growth retardation and hatchery diseases. Gut contents were collected from 158 day- old and six 14- week old runted/stunted broiler chickens in commercial farms (ten) and hatcheries (six) located in Southwest Nigeria. The samples were examined for the presence of chicken astrovirus (CAstV), avian nephritis virus (ANV), avian rotavirus (AvRV), chicken parvovirus (ChPV) and turkey astroviruses (TAstV-1 and -2) by polymerase chain reaction (PCR) and reverse transcriptase-PCR (RT-PCR) whereas avian reovirus (ARV) and fowl adenovirus (FAdV) by virus isolation (VI), RT-PCR and PCR. While CAstV was detected in all the birds (100%), sporadic detection of ANV (5%) and ChPV (5%) was observed in day-old and/or older birds. Four isolates were obtained by VI with one isolate being ARV positive and other three FAdV positive by RT-PCR and PCR, respectively. These findings strongly suggest CAstV as a major cause of runting and stunting as well as hatchery condemnations in commercial broilers in Southwest Nigeria, although co-infections with ANV, FAdV, ARV and ChPV cannot be ruled out. In addition, the possible vertical and horizontal transmissions of these viruses are discussed.